Hospitality English Vocabulary Mastery: A Qualitative Descriptive Study on Student Performance with Wordwall Games - Sabiku, Sri Ariyanti (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to evaluate English vocabulary mastery among tourism students in the hospitality sector. Seven key areas of vocabulary proficiency were assessed, encompassing basic hotel vocabulary, travel and tourism terminology, hotel systems and operations, hotel services and amenities, room types, marketing and promotion, and hotel department functions. A qualitative descriptive method was employed, involving 26 purposively sampled tourism students from Universitas Negeri Gorontalo during the even semester of the 2023-2024 academic year. Data were collected through direct observation and vocabulary tests, designed using four game-based activities on the Wordwall platform: wordsearch, anagram, gameshow quiz, and match-up. The findings reveal significant variation in vocabulary mastery across different topics. The